Hardware a systematic approach targeting data-intensive applications. - Wiangtong, T. (IEEE Signal processing magazine)
This article presents a systematic approach to hardware/software codesign targeting data-intensive applications. It focuses on the application processes that can be represented in directed acrylic graphs (DAGs) and use a synchronous dataflow (SDF) model, the popular form of dataflow employed in DSP systems when running the process. The codesign system is based on the ultrasonic reconfigurable platform, a system designed jointly at Imperial College and the SONY Broadcast Laboratory. This system is modeled as a loosely coupled structure consisting of a single instruction processor and multiple reconfigurable hardware elements. The paper also introduces and demonstrates a task-based hardware/software codesign environment specialized for real-time video applications. Both the automated partitioning and scheduling environment and the task manager program help to provide a fast robust for supporting demanding applications in the codesign system.